2019
DOI: 10.1186/s12885-019-6365-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurolymphomatosis of the lumbosacral plexus and its branches: case series and literature review

Abstract: BackgroundNeurolymphomatosis (NL) is a direct process of invasion of peripheral nerves by lymphoma. It occurs in roughly 5% of patients with lymphoma and represents a particularly difficult diagnostic dilemma when it is the presenting focal manifestation of occult lymphoma.Case presentationWe present 3 examples of invasion of the lumbosacral plexus and its branches. These cases demonstrate a protean clinical picture with regards to the time relationship to the clinical course of lymphoma and the neuroanatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…[6,7] In a previous review of the literature highlighting 23 cases of NL involving the lumbar / sacral nerves, nerve involvement was the primary finding, without evidence of solid organ involvement by lymphoma. [8] Additionally, in another larger series, only 11 of 72 patients diagnosed with NL were found to have concurrent systemic involvement by lymphoma. [1] Cases such as the one presented here highlight the importance of tissue diagnosis when a rare entity such as neurolymphomatosis is entertained, as well as a full systemic work up in suspected cases, as the neurologic manifestations may represent the cardinal sign of an undeclared occult lymphoma.…”
Section: Discussionmentioning
confidence: 93%
“…[6,7] In a previous review of the literature highlighting 23 cases of NL involving the lumbar / sacral nerves, nerve involvement was the primary finding, without evidence of solid organ involvement by lymphoma. [8] Additionally, in another larger series, only 11 of 72 patients diagnosed with NL were found to have concurrent systemic involvement by lymphoma. [1] Cases such as the one presented here highlight the importance of tissue diagnosis when a rare entity such as neurolymphomatosis is entertained, as well as a full systemic work up in suspected cases, as the neurologic manifestations may represent the cardinal sign of an undeclared occult lymphoma.…”
Section: Discussionmentioning
confidence: 93%
“…Concerning the anatomical localization of primary NL, isolated involvement of LSP is the first clinical manifestation of lymphoma in 74% cases of NL, with sciatic localization in all cases (9). The biopsy is often difficult to perform because not all of the nerves are accessible in a biopsy procedure and there is a possibility of a permanent large deficit, which probably contributes to underestimation of data on incidence of primary NL.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is another useful imaging tool for evaluating peripheral nerves. NL findings include diffuse or nodular thickening of nerves, T2 prolongation, and abnormal enhancement of nerve lesions [3,8]. We did not include these findings because recent studies of NL have reported diagnostic accuracies of 59-77% for MRI, which is inferior to those of 18 F-FDG PET/CT, which have been reported to be 84-100% [1,9].…”
Section: Discussionmentioning
confidence: 99%
“…Neurolymphomatosis (NL) is a rare condition that occurs in patients with malignant lymphoma (ML) and is characterized by the direct invasion of the peripheral nervous system by neoplasm cells. It is most observed in patients with non-Hodgkin's B-cell lymphoma (NHL), especially in cases of diffuse large B-cell lymphoma (DLBCL) [1][2][3]. Although the exact prevalence of NL is unknown, it is estimated to occur in approximately 0.2% of all NHL patients [2].…”
Section: Introductionmentioning
confidence: 99%